The Learn From Home and Alienation - Agustin Sukses Dakhi (Publisher Cv. Inara, 2020)
Since the outbreak of corona virus spread in the ground water, has an effect on the world of education. The government took the policy to learn from home then the process of learning takes place online or online with the use of various applications such as Zoom, WhatsApp, Google Classroom, Google Meet, Cisco Webex, including learning through TVRI. Thus already four months the students not to school, not with friends, not meet with the teacher, no learning process in the class room, not in the school environment. This study aims to describe the state of alienation or alienated experienced by students since the learning at home. Data collection techniques with interviews to Junior high school students around the town of teluk-dalam road. The results showed that the Junior high students around the town of teluk-dalam road experiencing the symptoms of alienation.